The impact of emergent public health events on passengers' public transport dependence. (September 2021) - Hu, Song; Lin, Pengfei; Weng, Jiancheng; Zhou, Wei
Abstract: Introduction: The optimization of public transport (PT) systems to ameliorate urban traffic problems and living environment requires a deep understanding of PT usage behaviour. However, there is a lack of scientific measurement of the influence on passengers' PT dependence (PTD) during emergent public health events. Methods: An extended theory of planned behaviour and an online survey scheme are proposed to investigate the influence of psychological and objective factors on passengers' PTD under an emergent public health event in Beijing, China. Then, four structural equation models are estimated to analyse the PTD influence mechanism of different groups of passengers. Results: The objective condition factors exert indirect effects on passengers' PTD via the psychological factors. Individual attributes have small influences on passengers' PTD, while the environment has a significant positive effect. Subjective norms have the highest influencing effect on passengers' PTD, and passengers with a relatively high PTD level have the risk of shifting to other transportation modes under the emergent public health events. Conclusions: The influence mechanism of emergency public health events on the PT dependence of different passengers is heterogeneous. The targeted policies should be implemented for different passengers to improve the PT market share and residents' health under emergent public health events. Highlights: Proposes an extended theoretical model framework based on the theory of planned behaviour. Highlights the significance of psychological and objective factors influencing passengers' public transport dependence. Indicates the negligible utility of residents' self-selection effect control during a public health crisis. Reveals the difference in the influence mechanism of public transport dependence among different travel groups.